2011
DOI: 10.1037/a0022061
|View full text |Cite
|
Sign up to set email alerts
|

Goal consensus and collaboration.

Abstract: This article updates our previous article in this journal (Tryon & Winograd, 2001) by examining via meta-analyses results of recent studies, published from 2000 through 2009, that relate goal consensus and collaboration to treatment outcome. Specifically, 15 studies with a total sample size of 1,302 yielded a goal consensus-psychotherapy outcome effect size of .34 (SD = .19, p < .0001, 95% confidence interval = .23-.45), indicating that better outcomes can be expected when patient and therapist agree on therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
82
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(88 citation statements)
references
References 47 publications
4
82
0
2
Order By: Relevance
“…The strength of the alliance demonstrates a modest but consistent impact on psychotherapy outcome, with meta-analytic effect sizes ranging from .22 to .27 (Horvath et al, 2011;Horvath & Symonds, 1991;Martin, Garske, & Davis, 2000). Additionally, metaanalytic findings (Tryon & Winograd, 2011) have demonstrated that patient and therapist agreement on the goals and tasks of therapy enhance treatment outcome (p. 34), as does engagement in an active cooperative relationship (p. 33). Researchers have concluded that the working alliance is an essential ingredient in producing therapeutic change (Horvath & Greenberg, 1986;Lambert & Barley, 2001;Lambert & Simon, 2008;Norcross, 2002).…”
Section: Empirical Researchmentioning
confidence: 98%
“…The strength of the alliance demonstrates a modest but consistent impact on psychotherapy outcome, with meta-analytic effect sizes ranging from .22 to .27 (Horvath et al, 2011;Horvath & Symonds, 1991;Martin, Garske, & Davis, 2000). Additionally, metaanalytic findings (Tryon & Winograd, 2011) have demonstrated that patient and therapist agreement on the goals and tasks of therapy enhance treatment outcome (p. 34), as does engagement in an active cooperative relationship (p. 33). Researchers have concluded that the working alliance is an essential ingredient in producing therapeutic change (Horvath & Greenberg, 1986;Lambert & Barley, 2001;Lambert & Simon, 2008;Norcross, 2002).…”
Section: Empirical Researchmentioning
confidence: 98%
“…Research has shown that therapy is most effective when goals are set collaboratively (Tryon & Winograd, 2011), but sex offenders who participate in structured group programmes rarely have any input into their therapy goals. When individuals have the opportunity to engage in open-ended groups (which allow greater individualisation of treatment) compared to closed groups (where the time spent on each therapeutic target is determined by the needs of the whole group), attrition rates are lower, and facilitators report they are able to develop more effective and enduring therapeutic relationships, thereby enhancing treatment processes (Ware, Mann, & Wakeling, 2009).…”
mentioning
confidence: 99%
“…For example, while studies have considered the causal benefits of including homework in CBT , correlational adherence-outcome relations (Kazantzis et al 2016;Mausbach et al 2010), and session-by-session benefits associated with homework adherence (Conklin and Strunk 2015), more research is needed on the in-session therapist behaviors that can facilitate engagement Startup and Edmonds 1994;and see;Shaw et al 1999 for evidence of competence in structuring sessions as a predictor of outcomes). Similarly, existing measures may not fully capture the definition of collaboration in CBT (Kazantzis et al 2015;Tryon and Winograd 2011), the evidence for Socratic dialogue is just emerging (Braun et al 2014), and study of feedback processes has centered on symptom assessments (Knaup et al 2009;Lambert and Shimokawa 2011).…”
Section: In-session Processesmentioning
confidence: 99%